Enhancing Emission Intensity of Spectral Lines Ti I Using Nanoparticle enhanced laser-induced breakdown spectroscopy (NELIBS) - Noory, Noor Kefah; Hamad, Tagreed; Al-abassi, Salam A. W. (Al-Nahrain Journal for Engineering Sciences, 2025)
Enhanced signal emission from nano (ESEN) coated titanium target over than that from normal untreated one was investigated. Four samples of Ti alloy were adjusted, the first sample was left untreated, the second and third samples were coated with plasma sputter at thicknesses of 35nm and 70nm, and the last sample was treated with a drop of colloidal Au nanoparticle solution prepared by laser ablation. The (ESEN) was monitored with Ti at 413.7 and 393.3 nm. It was obtained that the spectral emission from the nano-laser ablation had a greater improvement than that from the plasma sputter coating or bulk target. Enhancement factors were found up to ten folds, and show the spectroscopic line induced patterns by laser energies (100,150, and 200mJ) from the alloy with and without gold.